Crustal movement model in the ITRF2020 – a case study in Northern Vietnam - Bui Thi Hong Tham; Phi Truong Thanh (Записки Горного института)
In the North area of Vietnam, the crustal movement velocity of 38 GNSS points belonging to different international Earth reference frames (ITRF2000, ITRF2005, ITRF2008) is adjusted to the international Earth reference frame ITRF2020. This is the latest frame up to now. Since then, the picture of crustal movement in the North area of Vietnam has been unified in a dynamic coordinate system. In the study area, the rate of crustal movement is about 35 mm/year, and the direction of displacement is from northwest to southeast. To build a model of the crustal movement of the Earth in the northern area of Vietnam, the movement velocity data of 38 stations in ITRF2020 is evaluated with high accuracy. All points are also satisfactory. And then, the crustal movement velocity model is built by using the collocation method in the form of the 3-order Markov function. Within 38 stations, 34 stations are used to build the model and 4 remaining stations are used as checked stations. The obtained results show that the Earth's crust movement velocity model has an accuracy of about 2 mm/year for movement velocity and 2 deg for movement direction. This is the first model of Earth's crust movement in the North of Vietnam that has been built in the latest dynamic coordinate system ITRF2020. These results have important significance in the research and practical application of the movement of the Earth's crust. The steps of building the movement velocity model in this study can be applied to other experimental areas in the territory of Vietnam.